Pile design and construction rules of thumb - Rajapakse, Ruwan (Elsevier/Butterworth-Heinemann, 2008)
A complete reference covering virtually every aspect of the subject of pile design.
Keywords: Piling (Civil engineering); elektronické knihy; electronic books